2011
DOI: 10.1042/an20110011
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothesis: Are Neoplastic Macrophages/Microglia Present in Glioblastoma Multiforme?

Abstract: Most malignant brain tumours contain various numbers of cells with characteristics of activated or dysmorphic macrophages/microglia. These cells are generally considered part of the tumour stroma and are often described as TAM (tumour-associated macrophages). These types of cells are thought to either enhance or inhibit brain tumour progression. Recent evidence indicates that neoplastic cells with macrophage characteristics are found in numerous metastatic cancers of non-CNS (central nervous system) origin. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 118 publications
(245 reference statements)
2
67
0
Order By: Relevance
“…Increased expression of microglial Gfap, Vim and Serpina3n transcripts was also reported in a mouse model of ALS (Chiu et al, 2013), whilst in vivo microglial transformation into astrocyte-like cells were found in a rat model of the disease (Trias et al, 2013). Co-expression of microglia and astrocytic markers has been also found in neoplastic glioblastoma multiform cells associated with increased inflammation (Huysentruyt et al, 2011). Other studies had also shown vimentin expression in reative microglia following injury (Graeber et al, 1988; Wohl et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of microglial Gfap, Vim and Serpina3n transcripts was also reported in a mouse model of ALS (Chiu et al, 2013), whilst in vivo microglial transformation into astrocyte-like cells were found in a rat model of the disease (Trias et al, 2013). Co-expression of microglia and astrocytic markers has been also found in neoplastic glioblastoma multiform cells associated with increased inflammation (Huysentruyt et al, 2011). Other studies had also shown vimentin expression in reative microglia following injury (Graeber et al, 1988; Wohl et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We do feel that whatever the changes that occurred might offer some insight into overall cell transformation biology and perhaps to some understanding of forms of brain malignancy that may involve a microglial phenotype. Indeed, a recent review highlights a possible role of microglial transformation, in particular, in glioblastoma multiforme (Huysentruyt et al, 2011). Although our present report focused on the microglial phenotype characterization of the SIM-A9 cells, it would be of a great future interest to elucidate potential oncogenic factor(s) that prompted the transformation of the primary microglia.…”
Section: Discussionmentioning
confidence: 99%
“…A further viewpoint arises from the recent finding that subpopulations of cells within human gliomas, specifically GBM, are neoplastic macrophages/microglia [33]. Metastatic cancer cells retrieved in spontaneous mouse brain tumors appear to express multiple properties of macrophages [34], thus suggesting that the most aggressive cells in GBM may be neoplastic microglia/macrophages.…”
Section: Discussionmentioning
confidence: 99%